Consumer Protection Measures in Non-Life Insurance Contracts: A South African and Australasian Trend? - Samantha Huneberg (Obiter, 2019)
Consumer protection has gained prominence in many different industries worldwide. In South Africa, the consumer protection trend was first identified in the promulgation of the National Credit Act and the Consumer Protection Act. Extending protection to the insurance industry has not been far behind. In recent years, South Africa has promulgated new legislative measures specifically aimed at the protection of consumers in relation to insurance contracts (policyholders). This trend is fast becoming a worldwide phenomenon with both Australia and New Zealand also recognising the importance of consumer protection measures in their insurance legislation. This article considers the position in South Africa, Australia and New Zealand with regard to consumer protection measures in insurance legislation within the non-life insurance sphere.